PERENCANAAN STRATEGIS SISTEM INFORMASI PADA PUSAT PENANGANAN INSIDEN KEAMANAN INFORMASI SEKTOR PEMERINTAH - Setiawan, Ahmad Budi (Kementerian Komunikasi dan Informatika R.I., 2014)
Information security incident is a form of attack on the security of information that can occur in all sectors. The government sector is one of the targets of information security incidents. Central Government Information Security Incident Handling was established with the aim to address all forms of attacks on information security in government sector. The sustainability Central of Government Information Security Incident Handling (GovCSIRT) needs to be supported with information system infrastructure that's sophisticated and sufficiently. This research aims to create an information system strategic planning at the Center for Government Information Security Incident Handling. Implementation of Information Systems in an organization must adapt to the vision, mission, goals and needs of the organization. Therefore, the Information Systems Strategic Planning at the Government Information Security Management Center must be performed using appropriate methodologies. There are a wide variety of methodologies in information systems Strategic Planning. This study used a Cassidy methodology which is developed by Annita Cassidy. These results are used as input in the development of infrastructure or basic Information Systems Security Management Center Information Government to realize the use of ICT in a safe and convenient administration. The results of this research is used as input or recommendation in the development of the Government Information Security Incident Response Center to actualize the use of ICT in government that is safe and comfortable.